2001
DOI: 10.1128/jvi.75.16.7290-7304.2001
|View full text |Cite
|
Sign up to set email alerts
|

Construction, Safety, and Immunogenicity in Nonhuman Primates of a Chimeric Yellow Fever-Dengue Virus Tetravalent Vaccine

Abstract: We previously reported construction of a chimeric yellow fever-dengue type 2 virus (YF/DEN2) and determined its safety and protective efficacy in rhesus monkeys (F. Guirakhoo et al., J. Virol. 74:5477-5485, 2000). In this paper, we describe construction of three additional YF/DEN chimeras using premembrane (prM) and envelope (E) genes of wild-type (WT) clinical isolates: DEN1 (strain PUO359, isolated in 1980 in Thailand), DEN3 (strain PaH881/88, isolated in 1988 in Thailand), and DEN4 (strain 1228, isolated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
146
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(151 citation statements)
references
References 52 publications
3
146
1
Order By: Relevance
“…27 However, the opposite was not true, since prevaccination with DEN2 vaccine did not increase the seroconversion rate against YF vaccine. 8,33,34 The T-cell responses in this clinical trial were consistent with the neutralizing antibody responses in that both doses of vaccine stimulated similar T cell immune responses, and prior immunity to YF Phase 1 Study of Live Attenuated ChimeriVax TM -DEN2 Vaccine virus did not inhibit the T cell response to ChimeriVax™-DEN2. IFNγ responses were virtually the same for the 2 doses of ChimeriVax™-DEN2 (10 3 and 10 5 pfu).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…27 However, the opposite was not true, since prevaccination with DEN2 vaccine did not increase the seroconversion rate against YF vaccine. 8,33,34 The T-cell responses in this clinical trial were consistent with the neutralizing antibody responses in that both doses of vaccine stimulated similar T cell immune responses, and prior immunity to YF Phase 1 Study of Live Attenuated ChimeriVax TM -DEN2 Vaccine virus did not inhibit the T cell response to ChimeriVax™-DEN2. IFNγ responses were virtually the same for the 2 doses of ChimeriVax™-DEN2 (10 3 and 10 5 pfu).…”
Section: Discussionsupporting
confidence: 52%
“…7 ChimeriVax™-DEN2 is a live, attenuated, genetically engineered virus prepared by replacing the genes encoding the two structural proteins, premembrane (prM) and envelope (E), of the YF 17D vaccine virus with the corresponding genes of the DEN2 virus (strain PUO-218, isolated from a case of classical DF, Bangkok, Thailand). 8 It is a monovalent component of a tetravalent vaccine formulation 9 currently being investigated in a Phase 2 study. Preclinical studies have demonstrated that the ChimeriVax™-DEN2 virus was is not neurovirulent when administered to adult mice via the intracerebral (IC) route, is genetically stable in cell culture, induces low levels of viremia, and protects 100% of monkeys against wt DEN2 heterologous challenge upon a single SC immunization.…”
Section: Introductionmentioning
confidence: 99%
“…Transient expression of pSVprM H39R -E resulted in the formation of intracellular prM/E heterodimers and secretion of the prM and E proteins in a particulate form at similar levels to those of the parental construct. A HisRArg substitution at M39, in addition to two changes in the E protein, was identified in a chimeric DENV-1/YFV, which caused decreased viraemia in monkeys compared with the parental DENV-1 and YFV (Guirakhoo et al, 2001). The contribution of the M39 Arg mutation to the monkey attenuation phenotype has not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…36 Although the prM-E genes may vary among diverse flaviviruses by over 40% of the encoded amino acids, chimeric 17D viruses are still viable. The gene fusion is made at the signal peptidase cleavage site between C and prM and the signal peptidase site at the E and NS1 junction.…”
Section: Replacement Of Yf17d Structural Genes With Those Of Other Flmentioning
confidence: 99%